Pemetrexed Hinders Translation Inhibition upon Low Glucose in Non-Small Cell Lung Cancer Cells - Marie Piecyk; Mouna Triki; Pierre-Alexandre Laval; Helena Dragic; Laura Cussonneau; Joelle Fauvre; Cédric Duret; Nicolas Aznar; Toufic Renno; Serge N. Manié; Cédric Chaveroux; Carole Ferraro-Peyret (Metabolites, 2021)
Genetic alterations in non-small cell lung cancers (NSCLC) stimulate the generation of energy and biomass to promote tumor development. However, the efficacy of the translation process is finely regulated by stress sensors, themselves often controlled by nutrient availability and chemotoxic agents. Yet, the crosstalk between therapeutic treatment and glucose availability on cell mass generation remains understudied. Herein, we investigated the impact of pemetrexed (PEM) treatment, a first-line agent for NSCLC, on protein synthesis, depending on high or low glucose availability. PEM treatment drastically repressed cell mass and translation when glucose was abundant. Surprisingly, inhibition of protein synthesis caused by low glucose levels was partially dampened upon co-treatment with PEM. Moreover, PEM counteracted the elevation of the endoplasmic reticulum stress (ERS) signal produced upon low glucose availability, providing a molecular explanation for the differential impact of the drug on translation according to glucose levels. Collectively, these data indicate that the ERS constitutes a molecular crosstalk between microenvironmental stressors, contributing to translation reprogramming and proteostasis plasticity.